Minimally Invasive Treatment With a Patient Specific Implant in Reconstruction of Isolated Anterior Wall Fracture of the Frontal Sinus. Issue 1 (January 2021) - Helmers, Renée; Klop, Cornelis; Schreurs, Ruud; de Lange, Jan; Dubois, Leander
Abstract : Abstract: Isolated fractures of the anterior wall of the frontal sinus are most often treated through a coronal approach. Although the coronal approach is a relatively easy procedure, the size of the incision is causing more problems related to patient morbidity and recovery time than smaller approaches. A novel, minimal invasive procedure for reconstruction of the anterior wall fracture of the frontal sinus is presented in this article. An endoscopic assisted approach to camouflage the defect of the anterior wall and restore the contour of the frontal bone with a titanium patient specific implant is described in 2 patients. The aim of this procedure is to evaluate the effect on the operating time, recovery time, length of hospital stay and facial scarring compared to the conventional coronal approach. Postoperative evaluation was performed by superimposing pre and postoperative 3D stereophotographs and computed tomography scans. A distance map demonstrated an accurate reconstruction of the preoperatively planned contour. Postoperative recovery of both patients was quick and uneventful with no complications. The use of endoscopically inserted patient specific implant for contour reconstruction in anterior wall fractures of the frontal sinus seems to offer a predictable and minimal invasive alternative to the conventional approach. Abstract : Supplemental Digital Content is available in the text